2005
DOI: 10.1038/sj.bjp.0706178
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of attenuated endothelium‐dependent relaxation seen in rabbit intrapulmonary vein following chronic nitroglycerine administration

Abstract: 1 This study was undertaken to determine whether long-term in vivo administration of nitroglycerine (NTG) downregulates the endothelium-dependent relaxation induced by acetylcholine (ACh) in the rabbit intrapulmonary vein and, if so, whether the type 1 angiotensin II receptor (AT 1 R) blocker valsartan normalizes this downregulated relaxation. 2 In strips treated with the cyclooxygenase inhibitor diclofenac, ACh induced a relaxation only when the endothelium was intact. A small part of this ACh-induced relaxat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 39 publications
0
24
1
Order By: Relevance
“…Once "eNOS uncoupling" has been developed, eNOS becomes dysfunctional and produces superoxide rather than NO. 18,29,30 We found that L-NAME (an inhibitor of eNOS-dependent superoxide production) 29 attenuated superoxide production in the endothelial region (but not the medial region) of vein grafts, suggesting that "eNOS uncoupling" may have developed in our experimental autologous vein grafts. We demonstrated before that celiprolol, ␤-adrenoceptor antagonist inhibited the superoxide production in endothelial cells.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Once "eNOS uncoupling" has been developed, eNOS becomes dysfunctional and produces superoxide rather than NO. 18,29,30 We found that L-NAME (an inhibitor of eNOS-dependent superoxide production) 29 attenuated superoxide production in the endothelial region (but not the medial region) of vein grafts, suggesting that "eNOS uncoupling" may have developed in our experimental autologous vein grafts. We demonstrated before that celiprolol, ␤-adrenoceptor antagonist inhibited the superoxide production in endothelial cells.…”
Section: Discussionmentioning
confidence: 86%
“…Fluorescent 12-bit images were acquired and then analyzed using commercial software (LSM5 PASCAL), as previously reported. 18 The total fluorescence intensities obtained from the four areas (36 ϫ 36 pixels square) in each preparation were averaged, and this (ie, one value for each preparation) was used for subsequent analysis.…”
Section: Methodsmentioning
confidence: 99%
“…# p < 0.05, ## p < 0.01 versus the control group; ⁎p < 0.05, ⁎⁎p < 0.01 versus the high glucose group. [47,48]. We found that sarpogrelate may inhibit the development of "eNOS uncoupling", thus leading to an increase in the endotheliumderived NO function.…”
Section: Discussionmentioning
confidence: 89%
“…Fluorescent 12-bit images were acquired and then analyzed using commercial software (LSM5 PASCAL), as previously reported. 13,17 The total fluorescence intensities obtained from four areas (36 ϫ 36 pixels square) in each preparation were averaged, and this (ie, one value for each value) was used for subsequent analysis.…”
Section: Animalsmentioning
confidence: 99%
“…In some experiments, the endothelium was carefully removed by gentle rubbing of the intimal surface of the vessel using small pieces of razor blade, as previously described. 13,17 Circularly cut strips (0.7-0.8 mm long, 0.2 mm wide) were mounted horizontally in a small chamber and attached to a strain gauge (AE801; SensoNor a.s., Horten, Norway), allowing us to record isometric tension. The chamber (capacity, 0.3 ml) was perfused continuously with Krebs solution at a flow rate of 2 ml/minute.…”
Section: Animalsmentioning
confidence: 99%